Qualitative Analysis: Comparison of Growth and Development in Children with HIV/AIDS Living at Lentera Halfway House and Those Living at Home with Family in Surakarta - Vita Raraningrum; Argyo Demartoto; Supriyadi Hadi Respati (Masters Program in Public Health, 2016)
Background: Children with HIV/AIDS infection need optimal endurance to grow and develop. Optimal endurance is required to cope with threatening diseases. This study aimed to compare growth and development in children with HIV/AIDS living at Lentera halfway house and those living at home with family in Surakarta.Subjects and Method: This was a qualitative study with case study approach. The main study subjects were children with HIV/AIDS. The informants of this study included manager and care-givers at the Lentera halfway house, and parents. The informants were selected by snowball sampling. The dependent variables under study included bodyweight, CD4, fine and gross motoric development, stigma and discrimination, moral and religious development. The independent variable was place of care, i.e. halfway house or home with family. Except for bodyweight and CD4, the other remaining variables were collected by in-depth interview and observation. Bodyweight was measured by scale. CD4 was measured by chemical laboratory.Results: There was no difference in child growth living in the two places of care, with respect to bodyweight and CD4 count. The CD4 count was moderate indicating a moderate immunosuppressive state. Children with HIV/AIDS suffered stigma and discrimination more at halfway house than at home living with family. There was no difference in gross motoric development in children with HIV/AIDS living at the two places of care. Likewise, there was no difference in moral and religious development in children with HIV/AIDS living at the two places of care.Conclusion: Stigma and discrimination occur more often in children with HIV/AIDS that live at halfway house than at home with family. Bodyweight, CD4 count, gross motoric development, and moral and religious development are comparable in children with HIV/AIDS that live at halfway house and at home with family.Keywords: children with HIV/AIDS, halfway house, family, growth, developmentCorrespondence: Vita Raraningrum. School of Midwifery Rustida, Banyuwangi, East Java. Email: vitarara.11@gmail.comJournal of Epidemiology and Public Health (2016), 1(3): 175-181https://doi.org/10.26911/jepublichealth.2016.01.03.04